Produksi dalam Al-Quran dan Hadis: Konstruksi Konsep Etika Produksi dan Tinjauan Filosofis - Naeli Zakiyah Agustina; Alvina Dinda Marshellina; Baros Galang Jiwa; Kholilur Rahman (JURNAL ILMIAH NUSANTARA, 2026)
Production in Islamic economics is not merely understood as an economic activity to create added value, but also as a process that integrates ethical, social, and spiritual dimensions. However, in modern economic practices, production is often oriented toward material profit, neglecting the moral values that should serve as its fundamental basis. This study aims to examine the concept of production from the perspectives of the Qur’an and Hadith using a philosophical approach and to relate it to historical practices in Islamic civilization. The research employs a qualitative method with a library research approach by analyzing relevant literature sources, including classical Islamic texts and contemporary scholarly works. The findings indicate that production in Islam is grounded in the principles of tawhid, justice, responsibility, and professionalism, which are integrated within the framework of maqashid al-shariah. Furthermore, production is viewed as an act of worship aimed at achieving comprehensive welfare (falah), rather than merely generating economic profit. This study also reveals that the Islamic concept of production has a strong philosophical foundation encompassing ontological, epistemological, and axiological dimensions, and has been historically implemented during the era of Caliph Umar ibn Khattab and the Abbasid dynasty. The implications of this study suggest that integrating Islamic ethical values into modern production systems can contribute to developing a more just, sustainable, and socially beneficial economic system.